Extraction of High Economic Potential of Lipids from Heterotrophic Cultivation of Indigenous Aurantiochytrium Microalgae Strain - Suhendra, Suhendra; Anggraini, Lia; Nuryasari, Fazhar; Hutari, Andri; Anggraini, Irika Devi; Marno, Septhian (Universitas Ahmad Dahlan, 2023)
Aurantiochytrium microalgae has long been recognized as oleaginous microalgae since its capability to produce high content of lipids biomass. Produced lipids from cultivation process of Aurantiochytrium can contain high concentration of omega-3 docosahexanoic acid, hence valuable biomass from the Aurantiochytrium microalgae has the potential to be used as a source of raw materials for nutrition, cosmetics and medicines. Generally, Aurantiochytrium microalgae can be found in mangrove ecosystems. Even Indonesia is ranked as the largest mangrove in the world, but the use of Aurantiochytrium sp microalgae is rarely explored in Indonesia. In order to optimize biomass utiisation produced the cultivation process, there shall be an optimum extraction process. Therefore, this study present the optimization of lipids from the Aurantiochytrium sp microalgae. The isolate used in this research comes from Bunaken mangrove forest, North Sulawesi, Indonesia. The cultivation process consists of three steps, namely standing culture (SC, 48 hours), pre-culture (PC, 48 hours) and standing culture (SC, 120 hours). The cultivation took pace in an erlemeyer flask using orbital shaker with an orbital speed of 220 rpm at room temperature and pressure. The average dried biomass was 9.4 g/L. In addition to cultivation process, recent paper presents also an extraction methodology using organic solvents, namely methanol, chloroform, acetone, ethyl acetate, and n-hexane. The lipids fcation can be extracted with a minimum of 7% lipid and a maximum of 47% lipid. From this study, extraction using acetone-chloroform-ethyl acetate solvents resulted in the highest fraction of lipids from the extraction process of Aurantiochytrium biomass. Since the paper discussing the extraction process of native Indonesia strain of Aurantiochytrium microalgae has never been presented before, therefore this paper shall be valuable basis for further research in this field.